The Role of Microfinance in the Development of Small and Medium Enterprises (SMEs) - Asad Khan; Daniyal Inayat; Dr. Samra Kiran (Journal of Business & Tourism, 2021)
This work has tried to investigate the impact of microfinance on the development of SMEs). The primary data was collected through questionnaires from SMEs in Peshawar. The results show that microfinance plays a vital role in the revenue and profit growth of SMEs and reveals that SMEs with higher financial risk and lower levels of productivity are more likely to seek microcredit. Furthermore, the results suggest that firm characteristics including product innovation efforts and managerial and entrepreneurial attitudes are the key determinants of the likelihood of receiving microfinance. The main problems identified were lengthy documentation process, lack of information about the microcredit other security requirements.